Characterization of the reaction of decoupling ubiquinone with bovine mitochondrial respiratory complex I. Issue 8 (2nd August 2016) - Masuya, Takahiro; Okuda, Kenji; Murai, Masatoshi; Miyoshi, Hideto
Abstract: We previously produced the unique ubiquinone QT ("decoupling" quinone), the catalytic reduction of which in NADH-quinone oxidoreduction with bovine heart mitochondrial NADH-ubiquinone oxidoreductase (complex I) is completely decoupled from proton translocation across the membrane domain. This feature is markedly distinct from those of typical short-chain quinones such as ubiquinone-1. To further characterize the features of the QT reaction with complex I, we herein synthesized three QT analogs, QT2–QT4, and characterized their electron transfer reactions. We found that all aspects of electron transfer (e.g. electron-accepting activity and membrane potential formation) vary significantly among these analogs. The features of QT2 as decoupling quinone were slightly superior to those of original QT. Based on these results, we conclude that the bound positions of QTs within the quinone binding cavity susceptibly change depending on their side-chain structures, and the positions, in turn, govern the behavior of QTs as electron acceptors. Graphical abstract: : Decoupling ubiquinone